Discovering the regional innovation potential for Smart Specialization : the case of the two Baltic Sea Regions - Gedminaitė-Raudonė, Živile; Virkkala, Seija; Lankauskien​ė, Rita; Mariussen, Åge; Mäenpää, Antti (Taylor & Francis, 2022)
The EU Commission launched an innovation strategy called Smart Specialization in 2012. Smart Specialization is a framework for developing policies unleashing place-based economic potential. Evaluations, however, have shown that appropriate innovation policy decisions are difficult. There is an innovation policy potential that must first be unleashed. This article shows how the application of a method – connectivity analysis – developed through a Baltic Sea Region project ‘LARS – Learning Among Regions on Smart Specialization,’ can be used to support Smart Specialization. The method includes transnational comparisons and targeted policy recommendations for public sector institutions operating within various institutional frameworks and different clusters. It consists of instruments (gaps and factors) measuring collaboration through interviews of 141 quadruple-helix stakeholders across eight Baltic Sea regions.
Keywords: Baltic Sea Region; collaboration; Innovation potential; public policy; Quadruple Helix; Smart Specialization; fi=Aluetiede|en=Regional Studies|